FOLFOXIRI plus biologics in advanced colorectal cancer. (4th May 2019) - García-Alfonso, Pilar; Torres, Gabriela; García, Gonzalo; Gallego, Iria; Ortega, Laura; Sandoval, Carmen; Muñoz, Andrés; Lloansí, Ariadna
ABSTRACT: Introduction : The combination of oxaliplatin, irinotecan, fluorouracil (5-FU), and leucovorin (FOLFOXIRI) results in improved outcomes compared with standard chemotherapy when used in frontline to treat patients with metastatic colorectal cancer (mCRC). FOLFOXIRI has been recently combined with biologic agents aiming further improvement in outcomes. Areas covered : This manuscript provides a comprehensive review of the results achieved by the FOLFOXIRI+biologic combination when used as first-line treatment in patients with mCRC. The search retrieved 19 clinical trial reports and 7 ongoing trials. The results are discussed focusing on secondary resection of metastatic disease, impact of sidedness (right–left primary tumor site), and impact of biomarkers. Expert opinion : Panitumumab is the only biologic that has proved its value when added to FOLFOXIRI in a randomized clinical trial. FOLFOXIRI-bevacizumab has the widest data from two large randomized phase III trials, being an option to be used in both the palliative and the conversion-therapy settings. However, the true benefit from adding bevacizumab remains to be established as it has not been evaluated in a randomized setting yet. Data on response rates and secondary resection rates are promising with the FOLFOXIRI-anti-EGFR combinations and may constitute a valuable option. Results of ongoing head-to-head studies will shed additional light on this issue.